Java, Indonesia and Islam - Woodward, Mark (Springer, 2011)
Mark R. Woodward's Islam in Java: Normative Piety and Mysticism in the Sultanate of Yogyakarta (1989) was one of the most important works on Indonesian Islam of the era. This new volume builds on the earlier study, but also goes beyond it in important ways. Written on the basis of Woodward's thirty years of research on Javanese Islam in a Yogyakarta (south-central Java) setting, the book presents a much-needed collection of essays concerning Javanese Islamic texts, ritual, sacred space, situated in Javanese and Indonesian political contexts. With a number of entirely new essays as well as significantly revised versions of essays this book is a valuable contribution to the academic community by an eminent anthropologist and key authority on Islamic religion and culture in Java. - Publisher's description.